Fluorescence Resonance Energy Transfer-Sensitized Emission of Yellow Cameleon 3.60 Reveals Root Zone-Specific Calcium Signatures in Arabidopsis in Response to Aluminum and Other Trivalent Cations(1)([W])([OA]) - Rincón-Zachary, Magaly (American Society of Plant Biologists, 2010)
Fluorescence resonance energy transfer-sensitized emission of the yellow cameleon 3.60 was used to study the dynamics of cytoplasmic calcium ([Ca(2+)](cyt)) in different zones of living Arabidopsis (Arabidopsis thaliana) roots. Transient elevations of [Ca(2+)](cyt) were observed in response to glutamic acid (Glu), ATP, and aluminum (Al(3+)). Each chemical induced a [Ca(2+)](cyt) signature that differed among the three treatments in regard to the onset, duration, and shape of the response. Glu and ATP triggered patterns of [Ca(2+)](cyt) increases that were similar among the different root zones, whereas Al(3+) evoked [Ca(2+)](cyt) transients that had monophasic and biphasic shapes, most notably in the root transition zone. The Al(3+)-induced [Ca(2+)](cyt) increases generally started in the maturation zone and propagated toward the cap, while the earliest [Ca(2+)](cyt) response after Glu or ATP treatment occurred in an area that encompassed the meristem and elongation zone. The biphasic [Ca(2+)](cyt) signature resulting from Al(3+) treatment originated mostly from cortical cells located at 300 to 500 μ m from the root tip, which could be triggered in part through ligand-gated Glu receptors. Lanthanum and gadolinium, cations commonly used as Ca(2+) channel blockers, elicited [Ca(2+)](cyt) responses similar to those induced by Al(3+). The trivalent ion-induced [Ca(2+)](cyt) signatures in roots of an Al(3+)-resistant and an Al(3+)-sensitive mutant were similar to those of wild-type plants, indicating that the early [Ca(2+)](cyt) changes we report here may not be tightly linked to Al(3+) toxicity but rather to a general response to trivalent cations.